Investigating the Impact of Emotional Intelligence on Academic Performance of Engineering Students: An Exploratory Study in Pakistan - Fakhar, A.; Jahanzaib, M.; Sarfraz, M.H.; Shafiq, M.; Rizwan, A. (The Nucleus, 2020)
Emotional intelligence (EI) has become one of the leading predictors of human success in professional, personal and academic life. This study investigates the influence of emotional intelligence and its four domains (self-awareness, self-management, social-awareness and social-management) on academic performance (AP) of engineering students. The data for this research have been collected through a structured questionnaire from 350 students of public and private sector engineering universities of northern Punjab Pakistan. The results from analysis of variance (ANOVA) and correlation statistics support the developed hypotheses by indicating positive influence of emotional intelligence on academic performance. Furthermore, senior students are found to be more emotionally intelligent than junior students. Also, the public sector engineering universities provide better environment for the promotion of emotional intelligence as compared to private universities. However, the level of emotional intelligence both at public and private universities needs to be improved. This study also provides a framework for improving emotional intelligence of the students.